Nanozyme Hydrogels for Self-Augmented Sonodynamic/Photothermal Combination Therapy - Wang, Shuntao; Zeng, Ning; Zhang, Qi; Chen, Mingzhu; Huang, Qinqin (Frontiers in Oncology, 2022)
Sonosensitizer-mediated sonodynamic therapy (SDT) has emerged as a promising anti-tumor strategy. However, this strategy of continuous oxygen consumption further exacerbates the hypoxic tumor microenvironment, which limits its therapeutic efficacy. In this study, we designed a multifunctional hydrogel (PB+Ce6@Hy) that simultaneously co-delivers nanozyme prussian blue (PB) and sonosensitizer chlorin e6 (Ce6) for the realization of photothermal therapy (PTT) and enhanced SDT. When the hydrogel reaches the tumor tissue through local injection, the 808 nm laser can induce the hydrogel to warm up and soften, thereby triggering the release of PB and Ce6. PB can interact with endogenous H2O2 in situ and generate sufficient oxygen to promote the Ce6-mediated SDT effect. Besides, due to the good encapsulation ability of the hydrogel, the nanomaterials can be released in a controlled manner by changing laser parameter, irradiation time, etc. The experimental results show that the PB+Ce6@Hy system we developed can generate a large amount of reactive oxygen species (ROS), which can be combined with the photothermal effect to kill tumor cells, as a result, tumor proliferation has been adequately inhibited. This combined PTT/SDT dynamic strategy provides a new perspective for Ce6-induced cancer therapy, showing great potential for clinical application.